Problems of Supply Chain Management Formation of Mega-Regional Free Trade Zones - Chuvakhina L.G.; Pospelov V.K.; Mironova V.N.; Sumarokov E.V. (International Journal of Supply Chain Management, 2019)
Abstract— One of the directions of the trade integration process of the economies of countries is the conclusion of multilateral and bilateral free trade agreements, the number of which is steadily growing and becoming an important factor in socio-economic development. Mutually beneficial terms of cooperation on a wide range of foreign economic relations that go beyond the limits of foreign trade operations for the supply chain management are determined and formed. Free movement of factors of production, support for fair competition, the protection of intellectual property rights, the cooperation in the field of industrial, scientific, technical and innovation interaction, the coordination and unification of the legislative framework of foreign economic policy form the basis of trade agreements between countries. However, the processes occurring in the global economy, caused primarily by the reluctance of the American leadership to hear other world trading players, frank calls for anti-trade trends in globalization cannot but provoke criticism from traditional American trading partners and closest political allies. Building a regional trade without the United States could lead to a whole coalition of former allies, from Canada to Great Britain, participating in trade wars against the Americans.